IMPORTANCE OF COMMUNAL INTELLECTUAL PROPERTY REGISTRATION IN FOSTERING CREATIVE ECONOMY IN BERAU'S DANCE COMMUNITY - Hediati, Febri Noor; Masnawiyah; Haifa Salsabila Mawardi (Law Research Review Quarterly, 2025)
The preservation and protection of traditional dance as a communal intelectual property (CIP). The dance comunity plays a significant role in sustaining cultural heritage while contributing to the region's economic growth through performances at festivals and events. However, the lack of awareness and legal protection for traditional dance has led to cases of ownership claims by external parties, threatening the authenticity and economic potential of these artistic expressions. this study employs a social legal reseach approach, incorporating qualitative data form field observations and questionnaires distributed among the dance communities in Berau regency. Findings indicate the a majority of dance group lack knowledge of communal intelectual property  rights, with 92 % of respondents unaware of the registration process. Additionaly, 84 % have experienced claims on their traditional dances, highlighting the urgency of legal recognition. registering communal intelectual property provides legal security, enhances economic opportunites and fosters innovation within the creative industry. It ensures the dance communities benefit from their artistic works through licensing, royalties and tourism promotion. Moreover, goverment intervention is necessary to facilitate the registration process, integrate communal intelectual property into regional development plans and provide education on property rights. This research underscores the importance of communal intelectual property registration as a strategic tool for cultural preservation and economic empowerment. Strengthening legal frameworks and increasing awareness among dance communities are crucial to safeguarding traditional arts while advancing the creative economy in Berau Regency.